Copper-promoted cyanation of aryl iodides with N, N-dimethyl aminomalononitrile. (16th February 2021) - Liu, Si-Zhan; Li, Jing; Xue, Cao-Gen; Xu, Xue-Tao; Lei, Lin-Sheng; Huo, Chen-Yu; Wang, Zhen; Wang, Shao-Hua
Graphical abstract: Highlights: An efficient and simple method on the construction of aryl cyanides has been developed. Different from most known strategies, no additive was needed in this reaction. N, N -Dimethylaminomalononitrile was used as the cyanide source with moderate toxicity and better stability. Abstract: A copper-promoted cyanation of aryl iodides has been successfully developed by using N, N -dimethyl aminomalononitrile as the cyanide source with moderate toxicity and better stability. This reaction features broad substrate scope, excellent reaction yields, readily available catalyst, and simple reaction conditions.